Potential impact on fertility of new systemic therapies for cystic fibrosis. (October 2015) - Jones, Gareth Huw; Walshaw, Martin John
Summary: Cystic fibrosis is primarily considered a respiratory disease with superadded pancreatic dysfunction; however the underlying genetic mutation results in the abnormal function of cells throughout the body – including tissues involved in reproduction. Practically all males and up to 50% of females with CF will suffer fertility issues – the causes of which are multifactorial and could be improved by treatments that target the underlying physiological deficit, such as ivacaftor. We consider the mechanisms by which the rapidly developing field of systemic treatments for CF could impact on the fertility of this group and review the available real world evidence.